What Can be Learned from a Local Stream? - Bedford, Alan (Marino Institute of Education, 2020)
The Irish primary curriculum, described as an “anthology of subjects”, is overloaded, often to the detriment of teachers, school management and most importantly, the students. There is a need for a more integrated approach to the curriculum, one which could be provided by incorporating outdoor Inquiry-Based Learning (IBL) in schools’ local environments. This study had two key aims: 1) to investigate if a school’s local environment provides opportunities to stimulate IBL and 2) to examine if primary school students are impacted by engaging in IBL, and how. A qualitative approach was followed, in order to evaluate the learning experiences of 4th Class primary school students during a case-study of outdoor IBL. A variety of research instruments were used to capture the data including observation during site visits, photographs, interviews, and children’s work samples, which led to some rich data being generated, powerful insights being recorded and offered a window into the mind of some inquisitive young learners. The findings illustrated that a school’s local environment can be a rich resource for education. By studying the local history, geography, science and/ or environmental issues through IBL, children can make meaningful connections to their own life, leading to a deeper level of engagement and conceptual understanding. Children were increasingly motivated, engaged and generally more content during the outdoor IBL. This research may prove useful to IBL practitioners, teachers, Irish policy makers and anyone with an interest in education.
Keywords: inquiry based learning; primary school; outdoor IBL